U.S. International Economic Strategy in a Turbulent World Strategic Rethink - Shatz, Howard J. (RAND Corporation, 2016)
This report presents strategic choices America faces regarding the international economy over the term of the next U.S. administration, focusing on policy choices in the areas of maintaining and improving the rules-based international economic system; working with China and better integrating it into the existing system; supporting economic growth of allies and partners; and using sanctions to change unwanted behavior and counter adversaries.